Impact of Foreign Direct Investment, Rising Oil Prices, and Industry Value Added on Economic Growth of Pakistan - Mehmood, Khawaja Asif; Iqbal, Ahsan; Bashir, Furrukh; Ahmad, Rashid (iRASD Journal of Economics, 2022)
Rising oil prices, foreign direct investment, and industrial value-added are the key component that affects the economic stature of a country. This study locates the relationship between FDI, rising oil prices, and industry value added on the economic growth of Pakistan. To do the analyses, data length ranging from 1980 to 2020 was used. For the regression results, the analytical technique of Autoregressive Distributed Lag (ARDL) is incorporated. The empirical results show that FDI encourages economic growth. Nevertheless, industry value added is also located for positive affectation on economic growth. However, rising oil prices are found to have negative effects on economic growth. Similarly, the combined effect of oil prices and FDI are found discouraging for economic growth. As a policy option, the government of Pakistan must need to encourage FDI inflows and should step up toward industrialization. On the other side, rising oil prices be controlled at the maximum extent as it is damaging to economic prosperity.